Role of Solid-State Materials in Development of devices for Internet of Medical Things - Anantham Srujana Jyothi; K.V.V. Subba Rao; Manas Kumar Yogi (International Journal of Solid State Innovations & Research, 2025)
The Internet of Medical Things (IoMT) represents a transformative paradigm in healthcare delivery, integrating connected medical devices, sensors, and wearable technologies to enable real-time patient monitoring and personalized treatment. Solid-state materials form the foundational infrastructure of IoMT systems, encompassing semiconductors, energy storage materials, sensing materials, and flexible electronics. This article explores the critical role of advanced solid-state materials in enabling miniaturization, energy efficiency, biocompatibility, and enhanced sensing capabilities essential for IoMT applications. The discussion encompasses semiconductor materials for processing and communication, energy storage solutions including solid-state batteries and supercapacitors, sensing materials for bio signal detection, and flexible substrates for wearable devices. Integration challenges, including biocompatibility, power management, and data security, are examined alongside emerging material innovations such as two-dimensional materials, perovskites, and biodegradable electronics. The convergence of materials science and healthcare technology promises unprecedented opportunities for continuous health monitoring, early disease detection, and improved patient outcomes in the era of connected medicine.
Keywords: Crystal; IoMT; Solid; nanomaterials; polymer; sensor